2004
DOI: 10.1519/r-13953.1
|View full text |Cite
|
Sign up to set email alerts
|

Can Albuterol Help Resistance Exercise Attenuate Unloading-Induced Bone Loss?

Abstract: Hind-limb-suspended rats incur attenuated bone loss with beta(2)-agonists, and humans note similar changes with concurrent resistance exercise. To examine if the beta(2)-agonist albuterol helps resistance exercise reduce unloading-induced bone loss, human subjects performed 40 days of unilateral limb suspension with their left legs, otherwise refraining from normal ambulatory activity. While performing left leg strength training 3 days.week(-1), subjects received a concurrent placebo or albuterol (16 mg.day(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Using a unilateral limb-suspension model in humans the effect of resistive exercise with or without administration of the b 2 -agonist albuterol during a 40-day experiment was examined (Caruso et al 2004). The outcome of the study is unclear, as there was no control group and the placebo group showed no change in BMC or lean mass of the suspended limb, as assessed by DXA.…”
Section: Pharmacological Countermeasuresmentioning
confidence: 99%
“…Using a unilateral limb-suspension model in humans the effect of resistive exercise with or without administration of the b 2 -agonist albuterol during a 40-day experiment was examined (Caruso et al 2004). The outcome of the study is unclear, as there was no control group and the placebo group showed no change in BMC or lean mass of the suspended limb, as assessed by DXA.…”
Section: Pharmacological Countermeasuresmentioning
confidence: 99%
“…The exercise prescription consisted of 2 MVCs (5 s duration), one set of 10 isotonic repetitions (*80% of 1RM), and a second set to muscle fatigue (Schulze et al 2002). Alternatively, four sets of 7-8 maximal concentric and eccentric muscle actions have been efficacious during 35-40 days of ULLS (Caruso et al 2004;Tesch et al 2004). Therefore, although exercise prescription is variable, high-load resistance exercise appears to be an effective countermeasure to unloading.…”
Section: Exercise Countermeasuresmentioning
confidence: 99%
“…In addition, studies are beginning to explore additional countermeasures that may optimize the benefit of exercise. For instance, when inertial flywheel resistance exercise was coupled with Albuterol (maximum dose *16 mg/day), bone mineral density in the unloaded limb was increased compared to flywheel resistance exercise alone (Caruso et al 2004). Albuterol is a B 2 -agonist that has previously shown to reduce bone loss during hind-limb unloading in animals (Bloomfield et al 1997).…”
Section: Exercise Countermeasuresmentioning
confidence: 99%
“…Indeed, both an increase 8 9 in suspended and denervated hindlimbs and a decrease under normal conditions [10][11][12][13] in bone density have been reported in animals after clenbuterol and salbutamol administration. Only one study has focused on humans 14 to determine if salbutamol helps resistance exercise to reduce unloading induced bone loss. The authors concluded that a resistance exercise/albuterol regimen probably increased bone mineral content by maintaining the mechanical loading stimulus.…”
mentioning
confidence: 99%